2020
DOI: 10.1177/2332858420912198
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Supporting Literacy Development Among English Learners: A Deep Dive Into the Role of Language Comprehension

Abstract: A distinguishing feature of English learners (ELs) centers on coming from homes in which a language other than or in addition to English is used, but bilingualism itself is not a risk factor for low academic achievement. Yet in the United States, ELs’ reading achievement continues to lag behind that of their English-proficient peers. In this introduction, I discuss the need for research that centers the role of language comprehension among ELs for understanding and supporting their literacy achievement, highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Based on our analysis of these data and anchored by the extant research that suggests the importance of foundational code‐focused skills as well as oral language and comprehension skills for EB students (Goldenberg, 2020; Mancilla‐Martinez & Lesaux, 2011/2017; Mancilla‐Martinez, 2020; Lesaux et al, 2010; Silverman et al, 2020), we offer the following recommendations for policy and practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our analysis of these data and anchored by the extant research that suggests the importance of foundational code‐focused skills as well as oral language and comprehension skills for EB students (Goldenberg, 2020; Mancilla‐Martinez & Lesaux, 2011/2017; Mancilla‐Martinez, 2020; Lesaux et al, 2010; Silverman et al, 2020), we offer the following recommendations for policy and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, these competencies include both code‐focused, foundational skills as well as language‐focused competencies related to oral language and linguistic comprehension. For code‐based, foundational skills, a preponderance of evidence has shown that explicit and systematic instruction in phonological awareness, decoding, and word recognition is effective for children learning to read in English (Foorman et al, 2019; Petscher et al, 2020) and it is well‐established that such code‐based foundational skills are a “nonnegotiable” (Mancilla‐Martinez, 2020) for EB children. Research syntheses focused on the effects of literacy instruction for EB children have shown strong evidence to support instruction in phonological awareness, alphabetic knowledge, decoding skill, and word reading (August & Shanahan, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, across our three partner schools, there was considerable overlap between Spanish-English bilingual students and students labeled as ELs. Prior to our partnership, the schools had not systematically assessed students' vocabulary knowledge, a finding that is not uncommon (Mancilla-Martinez, 2020). We knew vocabulary could not continue to be overlooked in our collaborative efforts to improve students' reading comprehension.…”
Section: Practice Partnershipmentioning
confidence: 99%